Case Report on Cryptorchidism with Small Penis Since Birth (Journal of Pharmaceutical Negative Results, 2022)
Background: Male sex glands that produce sperm and sex hormones are known as testicles (testes). Both testicles are usually found in the scrotum. Undescended testicle (UDT), also known as cryptorchidism, is a frequent reason for young males to be referred for urologic evaluation. The genitourinary tract is affected, and it is the most typical congenital defect. A 10-year-old male child is presented with a history of undescended testes with a small penis since birth. As per the narration of the parents, the child was born through full-term normal vaginal delivery with a birth weight of 3.2 kg. He was normally growing with the age but they came to know that the child’s penis is not growing as per age. On Physical Examination, abnormalities occur in the genital region. The non-palpable testicle was found along with the micropenis. Initially, the child is treated with hormonal therapy including Human Chorionic gonadotropin and the luteinizing hormone are given for 8 days. Orchiopexy is performed under general anesthesia by surgeons. A common condition in the pediatric population is cryptorchidism, which is characterized as the absence of at least one testis in the scrotum. Compared to the general population, patients with cryptorchids have a relative risk of testicular cancer that is approximately five times higher.